2012
DOI: 10.1080/07481187.2011.584025
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Bonds After Suicide Bereavement in Childhood

Abstract: It has been argued that the grieving process after suicide bereavement has unique properties (e.g.,J. R.Jordan, 2001). A qualitative study was conducted to explore one aspect of the grieving process--continuing bonds--after suicide bereavement in childhood. Data were collected through semi-structured interviews with 10 suicide-bereaved children and analyzed using Interpretative Phenomenological Analysis (Smith & Osborn, 2003). Three themes are discussed: thinking about the deceased, coping strategies, and ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…The results of this study are consistent with previous studies (e.g., Begley & Quayle, 2007;Harper et al, 2011;Wood et al, 2012) regarding continuing bonds as an important and helpful component of bereavement after suicide. Additionally, these findings align with previous studies (Kwilecki, 2011) and anecdotal evidence (Spencer-Thomas, 2010) regarding continuing bonds through after-death spiritual experiences among those bereaved by suicide.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study are consistent with previous studies (e.g., Begley & Quayle, 2007;Harper et al, 2011;Wood et al, 2012) regarding continuing bonds as an important and helpful component of bereavement after suicide. Additionally, these findings align with previous studies (Kwilecki, 2011) and anecdotal evidence (Spencer-Thomas, 2010) regarding continuing bonds through after-death spiritual experiences among those bereaved by suicide.…”
Section: Discussionsupporting
confidence: 92%
“…There has been some research examining continuing bonds among survivors of suicide loss. For example, Wood et al (2012), in their examination of children who had lost loved ones to suicide, found that many participants believed that the deceased continued to exist externally to them, and that this was a positive experience that often offered comfort. Similarly, Begley and Quayle (2007) reported that a common theme adults reported after losing a loved one to suicide was "purposefulness" (p. 32).…”
mentioning
confidence: 94%
“…The communication in the different materials has sometimes also been directly addressed to the deceased parent in what theoretically has been explained as a 'continued bond' (see Klass, Silverman and Nickman 1996;Neimeyer, Baldwin and Gillies 2006;Wood, Byram and Gosling 2012). Such after death communication was most frequently expressed in the Internet contexts (article III and IV), which seem particularly well-suited to this kind of perhaps more taboo expression.…”
Section: The Construction Of a Continued Bondmentioning
confidence: 99%
“…Hence, communication with an inner representation of the parent could function as a resource in grief through continued or reconnected attachment (Klass, Silverman and Nickman 1996;Neimeyer, Baldwin and Gillies 2006;Wood et al 2012). It is feasible that conflicts with the deceased parent related to the suicide itself and/or the relationship preceding the suicide might be addressed by the child and potentially resolved within this relationship.…”
Section: Support For a Continued Bond With The Deceased Parentmentioning
confidence: 99%
See 1 more Smart Citation